A Toolkit for Enhancing End-of-Life Care: An Examination of Implementation and Impact - Loeb, Susan J. (The prison journal, 2018)
The purpose of this study was to examine the infusion of a Toolkit for Enhancing End-of-Life Care in prisons, as well as the outcome and impact on the quality of prison end-of-life care. A total of 74 front-line staff and administrators were in attendance across two post-Toolkit-infusion evaluation visits. Applying qualitative analysis, co-researcher outcome findings were related to activities, community outreach and relations, multidisciplinary team, quality improvement approach, and participatory action research team effects. Organizational outcomes included barriers and challenges, cost, organizational features, sphere of influence, readiness (for change), and sustainability.